2006
DOI: 10.1007/s00210-006-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired in vivo venous constriction in conscious obese Zucker rats with metabolic syndrome

Abstract: The venous system plays a crucial role in regulating cardiac output and blood pressure. Although the relationship between obesity and hypertension is well recognized, little is known about the effect of obesity on venous function. We examined if 16-week-old obese Zucker rats, relative to age-matched lean Zucker rats, had altered in vivo venoconstriction to noradrenaline. The obese rats, compared to the controls, had higher mean arterial pressure (MAP), body weight, and plasma insulin and triglycerides, but red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Since MMP/TIMP-1 in diabetic group was greatly enhanced, which may underlie the change of vascular tissue due to degradation of extracelluar matrix, then the enhancement of vasoconstriction responses to NE. These results are in accordance with previous findings that aortic vasoconstriction was augmented in a db/db mouse model [31], [32], while in contrast to the findings that vasoconstriction was impaired in vivo in metabolic syndrome rats [33], and in other arteries of STZ-induced diabetes rats [34]. The possible reason of this controversy might be that the impairment of the NOS signaling involved in aortic function in hyperinsulinimic diabetic models is much greater than that in insulin-deficient ones [35].…”
Section: Discussionsupporting
confidence: 92%
“…Since MMP/TIMP-1 in diabetic group was greatly enhanced, which may underlie the change of vascular tissue due to degradation of extracelluar matrix, then the enhancement of vasoconstriction responses to NE. These results are in accordance with previous findings that aortic vasoconstriction was augmented in a db/db mouse model [31], [32], while in contrast to the findings that vasoconstriction was impaired in vivo in metabolic syndrome rats [33], and in other arteries of STZ-induced diabetes rats [34]. The possible reason of this controversy might be that the impairment of the NOS signaling involved in aortic function in hyperinsulinimic diabetic models is much greater than that in insulin-deficient ones [35].…”
Section: Discussionsupporting
confidence: 92%
“…Relation between obesity and hypertension is well known, but the effect of obesity on venous function is not clearly established. In an animal study, impaired in vivo venous pressor response has been shown 19 . We did not find primary influence of hypertension or hypothyroidism on the higher clinical scores of CVI in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found increased α-AR vascular reactivity in isolated and anaesthetised preparations from both type 1 and type 2 diabetic (20, 30, 38) and obese models (28, 29, 37). Alternatively, some studies reported unchanged [ 18 , 21 ] or reduced [ 43 , 44 ] vascular α-AR responses. However use of low phenylephrine doses that also failed to discern a difference in our study [ 18 ] or nonspecific α-AR stimulation with noradrenaline [ 43 , 44 ], may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some studies reported unchanged [ 18 , 21 ] or reduced [ 43 , 44 ] vascular α-AR responses. However use of low phenylephrine doses that also failed to discern a difference in our study [ 18 ] or nonspecific α-AR stimulation with noradrenaline [ 43 , 44 ], may explain these differences. The present study shows augmented vascular α-AR responsiveness, in magnitude and in duration, in conscious type 2 diabetic and obese animals, at clinical doses of phenylephrine (32).…”
Section: Discussionmentioning
confidence: 99%